Taxonomy of the genus Peyerimhoffia Kieffer from Mainland China, with a description of seven new species (Diptera, Sciaridae) - Kai Shi; Junhao Huang; Su-Jiong Zhang; Hong Wu (ZooKeys, 2014)
The taxonomy of the genus Peyerimhoffia Kieffer in China was studied. Eight species were recognized, including seven new species that are herein described and illustrated: P. hamata sp. n., P. obesa sp. n., P.sparsula sp. n., P. longiprojecta sp. n., P. brachypodua sp. n., P. yunnana sp. n., and P. shennongjiana sp.n. In addition, P. vagabunda (Winnertz, 1867) is reported for the first time from China. A key to these Chinese species is provided.